2017
DOI: 10.1111/pace.12987
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular Two‐Incision Technique for Subcutaneous Implantable Cardioverter Defibrillator Implantation: Results from a Multicenter Registry

Abstract: Background: The traditional technique for subcutaneous implantable cardioverter defibrillator (S-ICD) implantation, which involves three incisions and a subcutaneous pocket (PACE 2017; 40:278-285) implantable cardioverter defibrillator complications, subcutaneous implantable cardioverter defibrillator (S-ICD), two-incision technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 12 publications
2
62
0
2
Order By: Relevance
“…All patients underwent device implantation in the standard fashion using either a 2-or 3-incision approach as described previously. 3,[8][9][10][11][12] Briefly, the lateral pocket incision was made at the midaxillary line between the fourth and sixth intercostal space using a #10 blade.…”
Section: Device Implantationmentioning
confidence: 99%
“…All patients underwent device implantation in the standard fashion using either a 2-or 3-incision approach as described previously. 3,[8][9][10][11][12] Briefly, the lateral pocket incision was made at the midaxillary line between the fourth and sixth intercostal space using a #10 blade.…”
Section: Device Implantationmentioning
confidence: 99%
“…The two-incision approach creates an intermuscular pocket for the pulse generator rather than a subcutaneous pocket by incising the inframammary crease at the anterior border of the latissimus dorsi, allowing the generator to fit between the two muscles. Then a small incision at the xiphoid process (in the same direction as pocket incision) allows an electrode insertion device to tunnel the lead in place [8,9]. In a study of 36 patients, the two-incision approach was found to be safe and effective and it may produce superior cosmetic results compared to the three-incision approach [9].…”
Section: Implant Techniques and Considerationsmentioning
confidence: 99%
“…Then a small incision at the xiphoid process (in the same direction as pocket incision) allows an electrode insertion device to tunnel the lead in place [8,9]. In a study of 36 patients, the two-incision approach was found to be safe and effective and it may produce superior cosmetic results compared to the three-incision approach [9]. See Figure 2.…”
Section: Implant Techniques and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The subcutaneous implantable cardioverter defibrillator (S-ICD) was developed as an alternative therapy to T-ICD system, as it is a fully subcutaneous system without any transvenous or epicardial leads. 5,6 Thus, the S-ICD system has the potential to decrease periprocedural implantation risks, eliminate the problem of difficult venous access, reduce endovascular mechanical stress on leads, and decrease the risk of systemic device-related infection typically observed in patients with a T-ICD, even with the limit of lack of pacing capability as either antitachycardia pacing or sustained pacing for bradycardia. Therefore, S-ICD could play an important clinical role in a significant portion of patients with HF.…”
mentioning
confidence: 99%